Impact of integrating MSMEs business models in Kebumen regency during the Covid-19 pandemic - Wardani, Setia; Rianto, Rianto; Ashari, Anisa Fitri; Nurcahya, Gugum Gumilang (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
Micro, Small, and Medium Enterprises play an essential role in economic growth in Indonesia but have many obstacles in carrying out business processes. Capital, limited information, raw materials, access to investors, and sales systems are the main problems for MSMEs in Kebumen Regency. The COVID-19 pandemic has reduced the supply of raw materials due to policies implemented by the government to overcome the spread of COVID-19; besides that, MSMEs are faced with sales problems. At the beginning of the pandemic, many MSMEs experienced a very sharp decline in turnover, but MSMEs have the flexibility to survive in these conditions. This research aims to integrate a business model in the form of Supply Chain Management (SCM) to help develop business in MSMEs. The methods used include a qualitative approach using interviews before using and after using the business model. The results of the implementation of business model integration have obstacles, including aspects of education owned by MSME actors (40%), poor product quality (10%), investor access (30%), and capital (20%)